Fundamentalist Institutions and the Rise of Evangelical Protestantism, 1929–1942 - Carpenter, Joel A. (Church history, 1980)
In April of 1952 an article in Christian Life magazine proclaimed Chicago “the evangelical capital of the U.S.A.” To back this claim, editor Russell T. Hitt cited a host of evangelical agencies in greater Chicago: mission boards, denominational offices, colleges, Bible institutes, seminaries, publishing concerns (including Christian Life itself) and youth organizations. In total, the author mentioned over one hundred different agencies such as Youth For Christ International, the Slavic Gospel Association, Scripture Press and the Swedish Covenant Hospital. At first glance, the article appears to present a confusing list of unrelated organizations, but closer inspection reveals a coherent pattern.